If an original conditional statement is represented using pq, which represents the converse? ~p -> ~q ~q -> ~p q ->

Question

If an original conditional statement is represented using pq, which represents the converse?
~p -> ~q
~q -> ~p
q -> p
p -> q​

in progress 0
King 6 months 2021-08-04T13:27:09+00:00 1 Answers 10 views 0

Answers ( )

    0
    2021-08-04T13:29:08+00:00

    Answer: q -> p

    Step-by-step explanation:

    just took the test

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )